2019
DOI: 10.1556/650.2019.31496
|View full text |Cite
|
Sign up to set email alerts
|

A „kompromisszumos választás” szerepe a fogászati kezeléssel kapcsolatos döntések során. 676 magyar önkéntes részvételével végzett vizsgálat

Abstract: Introduction: The compromise effect is a well-known phenomenon in the world of marketing, but it is rarely examined in medical settings. In dental setting, the patient often has to make treatment-related decisions with price as the only available and comprehensible information to help informed choice. Aim: We sought to determine if the compromise effect plays a role in dental treatment choices, and if yes, how the effect is modified by factors such as perceived quality, professional jargon in the explanations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is well documented that dentofacial esthetics has a profound influence on one's social perception [1], and on self-perception as well [2][3][4]. For some time now, esthetics has been a central issue in dentistry, as patients put increasing emphasis on this aspect-sometimes prioritizing it over functional considerations [5,6]. This "esthetic turn" in patients' expectations prompted dental professionals to investigate what counts as esthetic in dentistry, both from the perspectives of the patient and the dentist.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that dentofacial esthetics has a profound influence on one's social perception [1], and on self-perception as well [2][3][4]. For some time now, esthetics has been a central issue in dentistry, as patients put increasing emphasis on this aspect-sometimes prioritizing it over functional considerations [5,6]. This "esthetic turn" in patients' expectations prompted dental professionals to investigate what counts as esthetic in dentistry, both from the perspectives of the patient and the dentist.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the quality of dentist-patient communication is related to patient satisfaction [ 20 , 21 , 22 ]. In the field of general medicine, studies have pointed out that patients prefer to be involved in the decision-making [ 23 , 24 , 25 ], and the few studies that are available on this specific question in dentistry, show the same [ 26 , 27 ]. It is also known that the perceived service quality influences patient loyalty through the effect of patient satisfaction which plays a key role in promoting patient loyalty [ 28 ].…”
Section: Introductionmentioning
confidence: 99%